(untitled) (International journal of artificial intelligence, 2026)
The analysis was carried out in children from 7 to 12 years of age of Secondary School No. 7 and children from 4 to 6 years of preschool No. 43, right-handed and left-handed (boys and girls). The results of the study showed that the highest growth rate of visual acuity in children with right-handed and left-handed (girls and boys) in childhood II was 9 years old (9.9%), while the lowest growth rate was 11 years old (2.1%). In the first period of childhood, however, no change in visual acuity was found when analyzed by gender.